Disclosure, venture capital and entrepreneurial spawning - Cumming, Douglas; Knill, April (Journal of International Business Studies, 2012)
Venture capital (VC) funds have been facing increasing regulatory scrutiny since the 2007 financial crisis, particularly with respect to calls for increased disclosure requirements. In this paper, we examine the effect of more stringent securities regulation on the supply and performance of VC, as well as on new business creation (i.e., entrepreneurial spawning). Using country-level and investment-level data from 34 countries over the years 2000–2008, we find that more stringent securities regulation is positively associated with the supply and performance of VC around the world. More stringent securities regulation is also positively associated with entrepreneurial spawning induced by VC. Among different forms of securities regulation, disclosure stands out as having the most economically meaningful impact, which casts doubt on the oft-repeated objections to disclosure in VC – that it would stifle the VC industry, because secrets would have to be revealed to competitors and the public. These findings are robust to numerous robustness checks for endogeneity. The policy implications are clear, however, regardless of endogeneity concerns: VC and entrepreneurship markets are enabled, not curtailed, in countries with better disclosure standards, when one compares the existing differences in disclosure around the world and changes thereto over the 2000–2008 period.